Expression of IL-20 Receptor Subunit β Is Linked to EAE Neuropathology and CNS Neuroinflammation - Dayton, Jacquelyn R.; Yuan, Yinyu; Pacumio, Lisa P.; Dorflinger, Bryce G.; Yoo, Samantha C.; Olson, Mariah J.; Hernández-Suárez, Sara I.; McMahon, Moira M.; Cruz-Orengo, Lillian (Frontiers in Cellular Neuroscience, 2021)
Considerable clinical evidence supports that increased BBB permeability is linked to immune extravasation to CNS parenchyma during neuroinflammation. Although BBB permeability and immune extravasation are known to be triggered by VEGF-A and CXCL12, respectively, the mechanisms that link both processes are still elusive. Signaling through the IL-20 cytokine has been implicated in VEGF–mediated angiogenesis and induces cellular responses through IL-20RB. Although dysregulated IL-20 signaling is implicated in many inflammatory pathologies, its contribution to neuroinflammation has not been reported. We hypothesize that IL-20 an all other members if this sub-family of cytokines plays a key role in CNS neuroinflammation by signaling through IL-20RB to induce VEGF activity and consequently enhancing BBB permeability and CXCL12-mediated immune extravasation. To address this hypothesis, we actively immunized IL-20RB-/-, IL-20+/- and wild-type mice to induce experimental autoimmune encephalomyelitis (EAE) and found that IL-20RB-/- mice showed amelioration of disease progression compared to IL-20+/- and wild-type EAE mice. Similarly, we passively immunized IL-20RB-/- and wild-type ‘host’ mice with myelin-reactive Th1 cells from IL-20RB-/- and wild-type ‘donor’ mice and IL-20RB-/- mice showed lesser disease progression than wild-type, regardless of the ‘donor’ myelin-reactive Th1 cells. However, treatment of C57BL/6 mice during EAE with neutralizing MABIL-20 was not remarkable. Using ELISA, we found detectable levels of all cytokines of the IL-20 sub-family within CNS tissues from IL-20RB-/-, IL-20+/- and wild-type mice. We also found distinctive alteration to IL-20 sub-family cytokines, IL-19, IL-20 and IL-24, expression pattern during EAE. Immunolabeling of CNS region-specific microvessels confirmed IL-20RB protein at the CNS microvasculature and upregulation during EAE. Microvessels isolated from macaques and human CNS tissues also expressed IL-20RB. Notably, HCMEC/D3 treated with IL-1 showed augmented expression of IL-20 receptor. Lastly, IL-20-treated HCMEC/D3 showed alterations on CXCL12 apicobasal polarity consistent with a neuroinflammatory status. This evidence suggests that IL-20 sub-family cytokines may signal at the BBB via IL-20RB, triggering neuroinflammation.